Two new fossil species of soldier beetles (Coleoptera, Cantharidae, Malthininae) from Baltic amber - Pankowski, Maximilian G.; Fanti, Fabrizio (Zootaxa, 2022)
Two new species of soldier beetles from the subfamily Malthininae—Malthinus masoni sp. nov. and Malthodes markpankowskii sp. nov.—are described from Baltic amber. Their discovery is yet more evidence of the remarkable number of Cantharidae in Europe during the Eocene. This diversity is likely the result of several forces, including the warmer climate that characterized the epoch as well as the wide variety of habitats where Baltic amber formed.